2021
DOI: 10.26451/abc.08.03.07.2021
|View full text |Cite
|
Sign up to set email alerts
|

Signal Competition in Dynamic Visual Environments: Relative Conspicuousness of Social Displays in the Jacky Dragon (Amphibolurus muricatus)

Abstract: Selection for conspicuousness has been an important force on visual signal design. Although signal efficacy has been extensively studied in acoustic systems, few studies have examined this attribute in dynamic visual signals. Here, I simulated signal competition between Jacky lizards (Amphibolurus muricatus) by presenting the motor patterns (tail-flick, push-up body rock, and slow arm wave) in isolation that are typically used in social communication. Phase 1 used four digital video playback systems to present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Overall, factors such as the vegetation structure and presence of predators seem to influence the signaling behavior of a population (Barquero, 2014; Ramos & Peters, 2017). Although the species relies on its cryptic coloration to avoid predators (Raynal et al, 2022), the visual displays have shown to be highly conspicuous (Woo, 2021). The signaling behavior of the species has been extensively studied and distinctive aggressive and submissive displays have been identified (Carpenter et al, 1970; Peters & Ord, 2003; Watt & Joss, 2003; Van Dyk & Evans, 2007; Barquero et al, 2015; Ramos & Peters, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, factors such as the vegetation structure and presence of predators seem to influence the signaling behavior of a population (Barquero, 2014; Ramos & Peters, 2017). Although the species relies on its cryptic coloration to avoid predators (Raynal et al, 2022), the visual displays have shown to be highly conspicuous (Woo, 2021). The signaling behavior of the species has been extensively studied and distinctive aggressive and submissive displays have been identified (Carpenter et al, 1970; Peters & Ord, 2003; Watt & Joss, 2003; Van Dyk & Evans, 2007; Barquero et al, 2015; Ramos & Peters, 2017).…”
Section: Introductionmentioning
confidence: 99%